Compact mechanically frequency and pattern reconfigurable patch antenna - Boukarkar, Abdelheq; Lin, Xian Qi; Jiang, Yuan; Chen, Yi Jun; Nie, Li Ying; Mei, Peng (IET microwaves, antennas & propagation, 2018)
The authors propose the design of a compact mechanically frequency and pattern reconfigurable patch antenna. The frequency tuning is achieved by changing the positions of two adjustable shorting screws which are used to modify the length of the antenna radiating patch. Simulated and measured results are carried out to validate the proposed approach. When the screws are symmetrically positioned, the measured operating frequency can be tuned from 2.95 to 5.16 GHz without degrading the radiation characteristics over the entire comparatively wide measured tuning range of 54.5%. The antenna main radiating beam can be tilted from θ = 0° to θ = 30° when the screws are asymmetrically positioned. The measured gains and efficiencies range from 3.01 to 5.53 dBi and 68 to 74%, respectively. The overall antenna size is only 0.39λ0 × 0.39λ0 × 0.02λ0.